Analisis Kebutuhan Anak Usia Dasar dalam Pembelajaran Berbasis Daring pada Masa Pandemi Covid-19 - Imam Hanafi (Maharot : Journal of Islamic Education, 2021)
This article aims to analyze the needs of basic age children in online-based learning during the Covid-19 pandemic. Research that tries to analyze the needs of basic age children in the context of survival, comfort, and well-being of life. Where the needs of basic age children in the learning system are very different from the needs of adults, especially when learning is carried out online. The research method uses a qualitative method of literature review. The results of the analysis show that the needs of basic age children include six aspects, namely physiological needs, the need for security, the need for love and attention, the need for rewards for achievements, the need for means for self-actualization, and the need for a sense of success. Therefore, online-based learning in the midst of the COVID-19 pandemic must pay attention to meeting the needs of children in terms of the ability to think and move, which is still very limited. This is the obligation of external parties. So parents and teachers must understand the level of needs and character of children in order to achieve learning goals, namely the formation of a person who is faithful, intelligent and has character even in the midst of a pandemic.